Administrative economies of scale in local government in Denmark: Sandy or sanded? - Houlberg, Kurt (Scandinavian Journal of Public Administration, 2011)
The Danish Local Government Reform in 2007 reduced the number of municipalities from 271 to 98 and the number of Regions from 14 to 5 along with major changes in tasks, finances and the equalisation scheme. One of the objectives of the reform was to realize administrative economies of scale. Measured by administrative costs, this article concludes that the amalgamated municipalities so far have not realized the expected administrative economies of scale. It is, however, also shown that the potential economies of scale prior to the Reform was inflated in a Reform legitimating process. Before as well as after the Reform, administrative economies of scale exist if analysing on administrative costs. Technically administrative costs by decentralised agencies, however, cannot be calculated and are therefore not included in the analysis. Basing the analysis instead on administrative personnel, including administrative staff employed at schools, kindergartens etc., the conclusion is that larger municipalities do not spend less resources on administration than smaller municipalities.